EP-420 Delayed primary repair of zone 2 flexor tendon injury after 4 weeks: Does it work?. (9th August 2022) - Labib, Amir; Lingamanaicker, Vidhya; Fay, Emily; Blakeway, Megan; Fleming, Andrew
Abstract: Aims: To report the outcomes of delayed primary repair of zone 2 flexor tendon injuries after 4 weeks. Methods: Retrospective evaluation of all adult patients presented with more than 4 weeks of flexor tendon injuries and underwent primary surgical repair between 2016 and 2019. Results: 271 patients' notes have been reviewed. Only 12 patients met the criteria. 70% of patients were male with a mean age of 25 years and 40% of them were manual workers. Knife laceration was by far the most common mechanism of injury. The little finger was the most affected finger followed by the ring and middle fingers. The mean time interval between initial injury and repair was 40 days. Only one infection was reported that was treated with oral antibiotics. Two cases were in need of tenolysis due to flexed contracture. The mean total active range of motion was 167. Patients reported a good functional outcome with a mean DASH score of 10. The number of hospital visits was 40% less compared with their counterparts who underwent two-stage reconstruction. Conclusions: In our experience, immediate reconstruction of delayed flexor tendon injuries is a better option for these cases. It is associated with a reasonable range of motion with fewer hospital visits. This facilitates early return to work, especially in the manual workers' population.